2011
DOI: 10.1007/s11692-011-9145-4
|View full text |Cite
|
Sign up to set email alerts
|

Hind Wing Shape Evolves Faster than Front Wing Shape in Calopteryx Damselflies

Abstract: Wing shape has been shown in a variety of species to be influenced by natural and sexual selection. In damselflies, front-and hind wings can beat independently, and functional differentiation may occur. Males of Calopteryx damselflies show species-specific nuptial flights that differ in colour signalling with the hind wings. Therefore, hind wing shape and colour may evolve in concert to improve colour display, independent of the front wings. We predicted that male hind wing shape evolves faster than front wing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 85 publications
1
28
1
Order By: Relevance
“…These contrasting results between fore-and hindwings suggest that foreand hindwings in Calopteryx damselflies are likely to have different roles during flight. Forewings are probably more involved in sustained flight and hindwings in signalling and manoeuvring in Calopteryx (Outomuro et al, 2012(Outomuro et al, , 2014. In support of this hypothesis, a previous study showed that hindwings, but not forewings, are essential for manoeuvring during flight in butterflies and moths (Jantzen & Eisner, 2008).…”
Section: Discussionmentioning
confidence: 80%
“…These contrasting results between fore-and hindwings suggest that foreand hindwings in Calopteryx damselflies are likely to have different roles during flight. Forewings are probably more involved in sustained flight and hindwings in signalling and manoeuvring in Calopteryx (Outomuro et al, 2012(Outomuro et al, , 2014. In support of this hypothesis, a previous study showed that hindwings, but not forewings, are essential for manoeuvring during flight in butterflies and moths (Jantzen & Eisner, 2008).…”
Section: Discussionmentioning
confidence: 80%
“…Although calopterygid males all have more or less short and broad wings, males still show a wide variation in wing morphology, which is related to wing size and coloration [28,45,46]. The present study differs from our previous works on wing shape in Calopterygidae [28,45,46] in that here we focus explicitly on the allometric effects on wing shape and the expected consequences on flight performance.…”
Section: Introductionmentioning
confidence: 94%
“…Many calopterygid males have wing coloration that is used for signaling in sexual selection processes [23,33-39] and species discrimination [40-42], and it is also selected by bird predators [43,44]. Although calopterygid males all have more or less short and broad wings, males still show a wide variation in wing morphology, which is related to wing size and coloration [28,45,46]. The present study differs from our previous works on wing shape in Calopterygidae [28,45,46] in that here we focus explicitly on the allometric effects on wing shape and the expected consequences on flight performance.…”
Section: Introductionmentioning
confidence: 99%
“…The present phylogenetic analysis is based on analysis of the mitochondrial gene cytochrome c oxidase subunit 1 (COI) and combined nuclear gene of the ribosomal ITS1–5.8S–ITS2 region (ITS). Wing shape and colour have been subjected to intense sexual selection pressure in calopterygids and are thus more important than genitalia and caudal appendages in classification (Cordoba‐Aguilar & Cordero‐Rivera, ; Eroukhmanoff et al ., ; Outomuro, Bokma & Johansson, ; Outomuro, Adams & Johansson, ). Morphometric analysis of calopterygid wing shape can yield useful information (Sadeghi, Adriaens & Dumont, ; Outomuro et al ., ).…”
Section: Introductionmentioning
confidence: 97%